2020
DOI: 10.3390/cancers12061352
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy Serial Monitoring of Treatment Responses and Relapse in Advanced Esophageal Squamous Cell Carcinoma

Abstract: (1) Background: Early predictive markers to track treatment responses are needed for advanced esophageal squamous cell carcinoma (ESCC) patients. We examined the prognostication and risk stratification role of liquid biopsy serial monitoring for this deadly cancer. (2) Methods: Circulating tumor cells (CTCs) and plasma cell-free DNA (cfDNA) were isolated from 60 ESCC patients treated by chemotherapy (CT) at five serial timepoints: baseline (CTC1/cfDNA1), CT pre-cycle III (CTC2/cfDNA2), CT post-cycle IV, end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The simplest technique of ccfDNA quantification is concentration reading with a fluorometer. Ko demonstrated that increasing ccfDNA concentration levels during two cycles of chemotherapy can predict early disease progression and poor outcomes [ 75 ]. On the other hand, the quantification of total ccfDNA presents a risk for the contamination of non-specific ccfDNA from normal tissue, which causes poor sensitivity and specificity for the diagnosis or prediction of cancer-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The simplest technique of ccfDNA quantification is concentration reading with a fluorometer. Ko demonstrated that increasing ccfDNA concentration levels during two cycles of chemotherapy can predict early disease progression and poor outcomes [ 75 ]. On the other hand, the quantification of total ccfDNA presents a risk for the contamination of non-specific ccfDNA from normal tissue, which causes poor sensitivity and specificity for the diagnosis or prediction of cancer-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were enrolled for OS analysis, with a total of 854 EC patients [ 13 , 25 , 26 , 27 , 29 , 32 , 54 , 75 , 82 , 83 , 84 , 85 ]. In this cohort, the average age was 63.6 years (61.5–66) and the median CTC positivity rate was 46.4% (18.0–79.7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously conducted technical validation and established clinical utilities of circulating tumor cells in colorectal, lung, breast, gastric, liver, prostate, esophageal, and nasopharyngeal cancers [27][28][29]. The clinical application of combining miRNA, circulating tumor cell [27][28][29], and bioinformatics technology [30,31] merits further exploration. To sum up, we discovered circulating microRNA signatures for identifying HCC and demonstrated the promising performance of the liquid biopsy assay for HCC identification and differential diagnosis.…”
Section: Supplementary Materialsmentioning
confidence: 99%